Health‐Related Quality of Life With Adjuvant Docetaxel‐ and Trastuzumab‐Based Regimens in Patients with Node‐Positive and High‐Risk Node‐Negative, HER2‐Positive Early Breast Cancer: Results from the BCIRG 006 Study. (28th June 2013) - Au, Heather‐Jane; Eiermann, Wolfgang; Robert, Nicholas J.; Pieńkowski, Tadeusz; Crown, John; Martin, Miguel; Pawlicki, Marek; Chan, Arlene; Mackey, John; Glaspy, John; Pintér, Tamás; Liu, Mei‐Ching; et al.
Abstract : Background: This study aims to describe and compare health‐related quality of life (HRQL) in patients with node‐positive and high‐risk node‐negative HER2‐positive early breast cancer receiving adjuvant docetaxel and trastuzumab‐based or docetaxel‐based regimens alone. Methods: Eligible patients ( n = 3, 222) were randomly assigned to either four cycles of adjuvant doxorubicin and cyclophosphamide followed by four cycles of docetaxel (AC→T) or one of two trastuzumab‐containing regimens: adjuvant doxorubicin and cyclophosphamide followed by docetaxel plus trastuzumab administered for 1 year (AC→TH) or six cycles of docetaxel plus carboplatin combined with trastuzumab administered for 1 year (TCH). The European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire C30 and BR‐23 were administered at baseline, the start of cycle 4 (mid), and the end of chemotherapy (EOC), as well as at 6, 12, and 24 months after chemotherapy. Results: Compliance rates for the EORTC questionnaires were acceptable at 72%–93% of eligible patients out to the 12‐month assessment. Systemic side effect (SE) change scores were significantly improved for TCH‐treated patients compared with AC→TH and AC→T at EOC, suggesting improved tolerability. Physical functioning (PF) was only slightly worse at midpoint for those receiving TCH, compared with patients who were just starting on taxane in an AC→TH regimen, but was otherwise similar between arms. All treatment arms recovered from the deterioration in SE, PF, and Global Health Scale scores by 1 year and median future perspective change scores continued to improve throughout treatment and follow‐up. Conclusion: HRQL outcomes for adjuvant docetaxel and trastuzumab‐based regimens are favorable and support TCH as a more tolerable treatment option. Abstract : In the BCIRG 006 trial, eligible patients were randomly assigned to either four cycles of adjuvant doxorubicin and cyclophosphamide followed by four cycles of docetaxel or one of two trastuzumab‐containing regimens: adjuvant doxorubicin and cyclophosphamide followed by docetaxel plus trastuzumab administered for 1 year or six cycles of docetaxel plus carboplatin combined with trastuzumab administered for 1 year. Health‐related quality‐of‐life outcomes for adjuvant docetaxel and trastuzumab‐based regimens were favorable and support docetaxel plus carboplatin combined with trastuzumab as a more tolerable treatment option. Abstract : 摘要 背景： 本研究旨在对接受基于多西他赛和曲妥珠单抗或仅基于多西他赛化疗的淋巴结阳性/高危淋巴结阴性的人表皮生长因子受体2（HER‐2）阳性早期乳腺癌患者的健康相关生活质量（HRQL）进行比较和描述。 方法： 符合标准的患者（ n = 3 222）被随机分组，接受4个疗程多柔比星和环磷酰胺辅助治疗继以4个疗程多西他赛化疗（AC→T）或下述2个含曲妥珠单抗的方案之一：多柔比星和环磷酰胺辅助治疗继以多西他赛和曲妥珠单抗化疗1年（AC→TH）或6个疗程多西他赛、卡铂和曲妥珠单抗联合化疗1年（TCH）。于基线、第4疗程开始时（中点）、化疗结束（EOC）和化疗结束后6个月、12个月和24个月时评测欧洲癌症研究与治疗组织（EORTC）生活质量问卷C30和BR‐23。 结果： 符合标准的患者在12个月评估时EORTC问卷的依从率良好（72% 93%）。EOC时，与接受AC→TH和AC→T化疗的患者相比，接受TCH化疗的患者全身不良反应（SE）变化评分显著改善，提示耐受性改善。中点时，TCH化疗患者的躯体功能（PF）仅稍劣于接受AC→TH化疗的患者（后者此时刚开始接受紫杉烷类治疗），但两组间PF相似。治疗1年时，各组患者的SE、PF和总体健康量表评分恶化均好转，对未来展望评分变化幅度的中位值在整个治疗和随访期间持续改善。 结论： 接受基于多西他赛和曲妥珠单抗辅助化疗患者的HRQL转归良好，且本研究支持TCH是一种耐受性更好的治疗选择。